2021
DOI: 10.1177/17423953211059143
|View full text |Cite
|
Sign up to set email alerts
|

Primary healthcare reform for chronic conditions in countries with high or very high human development index: A systematic review

Abstract: Objective To address the growing burden of chronic disease globally, many countries have developed a national policy for primary healthcare reform. In some countries with high and very high human development index, evaluations of the implementation of these reforms have been published. To date, there has been no systematic review of these evaluations. The objectives of this review are to identify: (a) the vision for primary healthcare; (b) the features of primary healthcare reforms; and (c) evaluation findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Assessments of the use of these advances have been published by several nations with high and extremely high human development indices. (18) Cohen et al (19) found several variables affecting the availability of evidence-based chronic illness therapy in primary care that meets guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Assessments of the use of these advances have been published by several nations with high and extremely high human development indices. (18) Cohen et al (19) found several variables affecting the availability of evidence-based chronic illness therapy in primary care that meets guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…General practice is the first point of contact for individual feeling ill in Irish health care system [ 1 ]. Structured general practice programmes for chronic disease management (CDM) have demonstrated benefits such as improved monitoring, better compliance and some improved outcomes [ 2 , 3 , 4 , 5 , 6 ]. Ireland’s Department of Health has identified structured care of chronic diseases in general practice as a core component of future health policy; in 2020 the Health Service Executive (HSE) established a CDM care system for general practice [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%